HUBUNGAN KUALITAS TIDUR DENGAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS DI PUSKESMAS TANAH TINGGI KOTA BINJAI TAHUN 2023 - Wahyuni, Sri; Leli, Leli Herawati (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Diabetes mellitus is a degenerative disease that increases rapidly and can attack almost the entire population. Diabetics have symptoms that make them uncomfortable, especially at night. The ability to maintain sleep quality can be explained by the length of sleep and the discomfort felt during sleep or when waking up. The aim of the research is to find out whether there is a relationship between sleep quality and blood sugar levels in diabetes mellitus patients at the Tanah Tinggi Community Health Center, Binjai City. The type of research used was correlation research with a cross sectional design, a population of 113 people, sampling using random sampling with a purposive sampling technique of 28 respondents suffering from type 2 diabetes mellitus. The data collection instrument was a questionnaire to measure the quality of the patient's sleep using the Pittsburgh questionnaire. Sleep Quality Index (PSQI) and measurement of instantaneous blood sugar levels (KGS) using a glucometer. Statistical testing of research data used the chi square statistical test with a significance limit (?) of 0.05 using the SPSS computerized system. The results of the study showed that the majority of diabetes mellitus patients' sleep quality was in the poor category, numbering 14 people (50.0%), and the majority of blood sugar level measurements in the abnormal category were 19 people (67.9%). The results of statistical tests using the chi-square test showed that the p value was 0.000 <0.005, so Ho was rejected and Ha was accepted, which means there is a significant relationship between sleep quality and blood sugar levels in diabetes mellitus patients at the Tanah Tinggi Binjai Community Health Center in 2023. Conclusions are based The results of research on the relationship between sleep quality and blood sugar levels in type 2 diabetes mellitus patients, there is a relationship between good sleep quality and normal blood sugar levels, so it is important to maintain a healthy lifestyle and good quality sleep.